The Application of Digital Leadership in Managing Public Political Participation on Social Media: A Case Study of the North Maluku Provincial Government’s Response - Nur Fauzi Zaahirah; Tessa Utari br Sinuraya; Erlangga Pramudya Pradana; Naufal Aji Satria (Eduvest - Journal of Universal Studies, 2026)
The increasing role of social media as a space for digital political participation allows direct interaction between the public and the government, yet the extent to which digital leadership can effectively manage this participation remains underexplored. This research aim to analyzes the application of digital leadership in responding to public political participation through social media with a case study on the TikTok account of the Governor of North Maluku, Sherly Tjoanda. This research used a qualitative approach with a case study method through social media mining techniques and qualitative content analysis of public comments. The analytical framework combines the concepts of digital leadership, online political participation, and responsiveness to see the relationship between leadership character, forms of participation, and government responses. The results of the study show that the digital leadership applied meets four main dimensions, namely message suitability, timeliness, technical mastery, and the ability to build relationships. Public participation is dominated by forms of activism/extra-representational voices that show the high involvement of citizens in conveying direct demands, especially related to infrastructure. In addition, the government's response has evolved from informal responses to substantive actions in the form of field visits, involvement of relevant agencies, and policy and budget adjustments. These findings confirm that social media can serve as an arena for effective political participation while encouraging government transparency and accountability, as well as strengthening the relationship between government and society in the digital age.